Analisa Perbandingan Kuat Tekan dan Kuat Lentur Beton FABA Sebagai Pengganti Agregat Dengan Variasi Mix design Untuk Mencapai Mutu Tinggi - Ramadiansah, Dani; Citra, Ika Revalia; Saputro, Yayan Adi; Hidayati, Nor (Jurnal Teknik Sipil, 2025)
This research utilizes waste from PLTU Tanjung Jati B Jepara, namely FABA (Fly ash Bottom Ash) as an alternative to fine and coarse aggregate. From this research, the physical properties of faba aggregate can be seen from the results of the faba aggregate sieve analysis test, which obtained a fineness modulus value of 1.74, which is included in the medium aggregate type. The water content of fine aggregate (fly ash) obtained a value of 3.63% and coarse aggregate (bottom ash) obtained a value of 1.5%. The fine aggregate sludge content (fly ash) obtained a value of 0%. The fine aggregate organic substance (fly ash) acquires a reddish brown NaOH color, therefore it must be washed before being used as a concrete mixture. The face dry specific gravity of fine aggregate (fly ash) obtained a value of 2.63 gr/cm2 and coarse aggregate 2.52 gr/cm2. From the data that has been obtained, faba aggregate is considered to have physical properties that meet the requirements for fine aggregate and can be used as a substitute for sand. The results of the final compressive strength of faba concrete and normal concrete at the age of 7 days and 28 days showed that the compressive strength of normal concrete (control) was higher than that of faba concrete. The standard deviation values ​​at the ages of 7 and 28 days are included in perfect working conditions because they have a standard deviation value of less than 3 MPa. From the results of the concrete flexural strength test, only the control concrete was 1;1.5 with a flexural strength of 4.18 MPa, which is close to SNI 2847:2013, namely with a minimum flexural strength of fs = 4.4 MPa. Normal concrete has a higher flexural strength than faba concrete. Based on tests carried out with the planned mix design, the 1:1.5 variation obtained the highest results.